Intestinal Gasdermins for regulation of inflammation and tumorigenesis - Gong, Wenbin; Yang, Kui; Zhao, Wei; Zheng, Jianbao; Yu, Junhui; Guo, Kun; Sun, Xuejun (Frontiers in Immunology, 2022)
Gasdermins (GSDMs) protein family express in intestinal epithelial cells or lamina propria immune cells, and play a nonnegligible function during gut homeostasis. With the gradually in-depth investigation of GSDMs protein family, the proteases that cleave GSDMA-E have been identified. Intestinal GSDMs-induced pyroptosis is demonstrated to play a crucial role in the removal of self-danger molecules and clearance of pathogenic organism infection by mediating inflammatory reaction and collapsing the protective niche for pathogens. Simultaneously, excessive pyroptosis leading to the release of cellular contents including inflammatory mediators into the extracellular environment, enhancing the mucosal immune response. GSDMs-driver pyroptosis also participates in a novel inflammatory cell death, PANoptosis, which makes a significant sense to the initiation and progression of gut diseases. Moreover, GSDMs are expressed in healthy intestinal tissue without obvious pyroptosis and inflammation, indicating the potential intrinsic physiological functions of GSDMs that independent of pyroptotic cell death during maintenance of intestinal homeostasis. This review provides an overview of the latest advances in the physiological and pathological properties of GSDMs, including its mediated pyroptosis, related PANoptosis, and inherent functions independent of pyroptosis, with a focus on their roles involved in intestinal inflammation and tumorigenesis.